Alcohol consumption as a factor associated with depression in students of human medicine of the Ricardo Palma university of the year 2018 - -Durand, Pedro Estrada (2019)
Objective: To determine whether alcohol consumption is a factor associated with depression in male medicine students at the Ricardo Palma del Ciclo II Private University (August-December) in 2018. Methods: Non-experimental, analytical, cross-sectional, descriptive, correlational study in the Human Medicine Faculty of the Ricardo Palma University, during the 2018 academic year. A survey and a validated test conducted 200 male students after their informed consent: The validated self-evaluation test of depressive features of Zung. which consists of 20 questions that help us determine the depressive state according to the diagnostic criteria ICD-10 and DSM IV. Results: 200 male students were surveyed. 67.5% of students are between 18 and 22 years old. 70% of students rarely consume alcohol, and 9% of students consume alcohol 2 to 6 times a week, 48.5% of students have mild depression and 3% of students have severe depression, in the group of students who have severe depression 50% consume alcohol 2 times a week, in the Chi square test the p-value (p = 0.000), which allow establishing that there is a significant relationship between alcohol consumption and depression in students Finally, it was found that the Odd Ratio (OR = 9.4) for Alcohol Consumption establishes that male students who consume alcohol more than once a week have a 9,444 higher risk of developing depression than male students who consume alcohol once a week. the week or less. Conclusion: Alcohol consumption is a risk factor associated with depression in male students of the Faculty of Medicine of the Ricardo Palma University.   DOI 10.25176/RFMH.v19.n1.1801